An approach to airline MRO operators planning and scheduling during aircraft line maintenance checks using discrete event simulation - Albakkoush, Salah Muftah M.; Pagone, Emanuele; Salonitis, Konstantinos (Elsevier, 2021)
The process of scheduling and planning refers to examining aircraft history based on when and where the aircraft should go for service checks. In this paper, the authors focused on line maintenance activities and examined the impact of unexpected factors (Missing tools and safety requirements) on such activities during the process through a Discrete Event Simulation (DES) model. The DES was used to determine the following: 1. The plan time of each maintenance task according to maintenance scheduling based on the X airline company in Libya; 2. A tasks and productivity evaluation which involved examining the number of tasks required to do per check according to the scheduling plan and planned tasks performed by technicians, and; 3. The total elapsed time involved by analysing the average time for each task according to maintenance schedule planning. The results show that, for all scenarios conducted, the DES model was operating at a high level, and in some scenarios, there was a breakdown in service tasks; a clear indication that the workload factor was high during check periods. However, the main finding in this study highlights how a number of different tasks or the breakdown of maintenance work packages were not being completed before the actual time that had been allocated for the general external condition A-check of the aircraft. This made it necessary to study the work package for each check separately and examine these work packages as they relate to DES which presents a potential solution to a more efficient planning approach. This feature enhances the applicability of the proposed method in real-life, and helps airlines cope with the dynamic environment of airline MRO.
Keywords: Line maintenance; maintenance scheduling; maintenance planning; maintenance work package; DES